New automobile monitoring and tracking model: Facilitate model with handhelds - Hameed, Shihab A.; Abdulla, Shaima; Ershad, Mohd; Zahudi, Fauzan; Hassan Abdalla Hashim, Aisha (2011)
One of the clear facts in the world is the increasing number of cars and other automobiles in term of production as well as theft attempts. There is a big effort done by many international and local companies to produce car security systems, but the result is still less than expectations since the number of car theft cases are still increases. The thieves are developing their capabilities and inventing smarter and stronger stealing techniques which require more powerful security systems. This research project proposes an Automobile Monitoring and Tracking Model to solve this issue. It introduces a powerful security model that can send SMS and MMS to the owner to have fast response especially if the car is nearby. This paper focuses on using MMS and database technology, the picture of the intruder will be sent to user or police. The Database offers the required information about car and owner, which will help police or security authorities in tracking the car using GPS system that can be link to Google Earth and other mapping software. The implementation and testing results show the success of prototype in sending MMS to owner within 40 seconds and receiving acknowledgment to the database (police or security unit) within 3-4 minutes. The timing and results are suitable to owner and police to take suitable action against intruder.